A randomised controlled clinical trial comparing the effectiveness of bandaging compared to the JuxtaCures™ device in the management of people with venous ulceration: Feasibility study. (August 2021) - Stather, Philip; Petty, Carroll; Langthorne, Helen; Rayner, Emma; Zhang, Jufen; Hayden, Karen; Howard, Adam
Introduction: The mainstay of treatment for venous ulceration remains compression therapy. Velcro Wrap devices are being increasingly used in these patients despite limited evidence. This feasibility study aimed to compare standard bandaging to the JuxtaCures™ Velcro wrap device. Methods: A single centre, unblinded RCT compared participants with venous ulceration randomised to either the JuxtaCures™ device or short stretch bandaging. Participants were followed up for 26 weeks. Results: 160 participants were screened with 40 randomised. 3 participants in bandaging and 1 in JuxtaCures™ didn't complete the study. 60% in JuxtaCures™ healed v 55% in bandaging despite larger ulcers in the JuxtaCures™ arm (9.33 cm 2 v 6.97 cm 2 ). There was no significant difference in time to healing (12.17 v 13.64 weeks). JuxtaCures™ showed improved ulcer reduction for those that didn't heal (14.91–5.00 cm 2 v 14.20–8.62 cm 2 ; P = 0.06). JuxtaCures™ had more consistent sub-bandage pressure dropping from 39–36 mmHg versus 41–25 mmHg in bandaging between application and removal (P < 0.001). Quality of life (EQ5D) was improved in JuxtaCures at 3 months (mean difference 0.14, p = 0.04), but not at 1 and 6 months, or in disease specific quality of life. Cost was lower in JuxtaCures™ £842.47 v £1064.68. Duration of appointment was significantly shorter in JuxtaCures™ (41 minutes v 53 minutes; P = 0.003). Conclusion: This study has shown the feasibility and necessity of running a multicentre trial to evaluate the use of Velcro wrap devices for venous ulceration. It highlights the potential benefits of more consistent pressure, increased self-care, and potential with regards to ulcer healing, cost, nursing resource and quality of life.